Building Social Capital and Leadership Skills for Sustainable Farmer Associations in Morocco - Catherine M. Rasmussen; Renee M. Pardello; John R. Vreyens; Scott Chazdon; Somongkol Teng; Michael Liepold (Journal of International Agricultural and Extension Education, 2017)
Agricultural development in Morocco relies on the economic strength of the country’s rural regions. Recently, government programs have focused special attention on actions encouraging farmer associations and strengthening value-chains for agricultural commodities. Small rural producers, however, lack the leadership skills and strategic planning capabilities to accomplish this initiative. The Morocco Rural Leadership Program connects University of Minnesota Extension staff with faculty at the National School of Agriculture, Meknès (ENA) in Morocco to co-design and teach a leadership cohort program for farmers. Its intent is to build social capital for sustainable value-chain development. Program evaluation revealed that the program not only increased leadership capacity but also grew farmers’ social capital and led to behavioral and procedural change in farmer associations.
Keywords: social capital; networks; leadership; sustainability; farmer associations; value chains; Morocco